Development of a functional human induced pluripotent stem cell-derived nociceptor MEA system as a pain model for analgesic drug testing - Nimbalkar, Siddharth; Guo, Xiufang; Colón, Alisha; Jackson, Max; Akanda, Nesar; Patel, Aakash; Grillo, Marcella; Hickman, James J. (Frontiers in Cell and Developmental Biology, 2023)
The control of severe or chronic pain has relied heavily on opioids and opioid abuse and addiction have recently become a major global health crisis. Therefore, it is imperative to develop new pain therapeutics which have comparable efficacy for pain suppression but lack of the harmful effects of opioids. Due to the nature of pain, any in vivo experiment is undesired even in animals. Recent developments in stem cell technology has enabled the differentiation of nociceptors from human induced pluripotent stem cells. This study sought to establish an in vitro functional induced pluripotent stem cells-derived nociceptor culture system integrated with microelectrode arrays for nociceptive drug testing. Nociceptors were differentiated from induced pluripotent stem cells utilizing a modified protocol and a medium was designed to ensure prolonged and stable nociceptor culture. These neurons expressed nociceptor markers as characterized by immunocytochemistry and responded to the exogenous toxin capsaicin and the endogenous neural modulator ATP, as demonstrated with patch clamp electrophysiology. These cells were also integrated with microelectrode arrays for analgesic drug testing to demonstrate their utilization in the preclinical drug screening process. The neural activity was induced by ATP to mimic clinically relevant pathological pain and then the analgesics Lidocaine and the opioid DAMGO were tested individually and both induced immediate silencing of the nociceptive activity. This human-based functional nociceptive system provides a valuable platform for investigating pathological pain and for evaluating effective analgesics in the search of opioid substitutes.